Laporan Kasus Manajemen Kegawatdaruratan Trauma Jaringan Lunak Wajah Pada Anak Penderita Talasemia - Fauzan Akmal; R Agus Nurwiadh; Eka Marwansyah Oli’i (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Facial soft tissue trauma is a common case in the emergency department. Handling this case requires special attention because the face is a prominent part and a marker of identity. Thalassemia is a blood disorder that causes the sufferer to experience anemia, where thalassemia patients must undergo blood transfusions for life. This case will describe a 14-year-old girl who came to the Emergency Department of Hasan Sadikin Hospital Bandung with complaints of bleeding on the eyelids due to a motorcycle accident, from the patient's history it is known that the patient is a thalassemia patient who routinely undergoes transfusions every month. As a result of this hemorrhage caused a significant decrease in hemoglobin value in the patient, so that emergency management was carried out, namely suturing the patient's traumatized eyelid and blood transfusion. Emergency management of facial soft tissue trauma in children with thalassemia must be done carefully to control bleeding and restore the function and aesthetics of traumatized facial tissues, besides that we also collaborate with pediatric colleagues for the management of anemia due to thalassemia in this patient.